Condition of Pancreas and Pancreatic Marker Following ModifiedBlumgart Pancreaticojejunostomy in Pancreaticoduodenectomy (The Planet, 2024)
Introduction: Pancreaticoduodenectomy (PD) is a complex surgical procedure primarily used to treat pancreatic and periampullary tumors. The Modified Blumgart Pancreaticojejunostomy (PJ) technique has emerged as a promising approach to minimize the incidence of POPF by enhancing the stability of pancreatic anastomosis. This study aims to assess the biochemical markers, particularly serum and drain fluid amylase levels, in the early postoperative period. Methods & Materials: This Cross-sectional Observational study was conducted among the indoor patients of surgery units in Dhaka Medical College & Hospital, Dhaka, from January 2023 to December 2023. All patients who experienced Pancreatoduodenectomy in the Surgery department of Dhaka Medical College & Hospital during the study period were considered as the study population. Result: This study involved 30 patients, with most (36.6%) aged between 40-50 years and a male predominance (63.3%). Pancreatic texture was hard in 53.3% of cases, while 46.6% had a soft texture. The majority (63.3%) had a pancreatic duct diameter of 6-8 mm. Postoperatively, serum amylase levels were normal in all patients, but 13.3% exhibited a significant rise in drain fluid amylase, indicating potential pancreatic fistula. Conclusion: In this study on the condition of the pancreas and pancreatic markers following Modified Blumgart Pancreaticojejunostomy in pancreaticoduodenectomy, 53.3% of patients had a hard pancreatic texture, and 63.3% had a duct diameter of 6-8 mm—both key factors affecting postoperative outcomes. A significant rise in drain fluid amylase, suggestive of pancreatic fistula, was observed in 13.3% of patients by postoperative day 3.
Keywords: Modified Blumgart Pancreaticojejunostomy; Pancreas; Serum Amylase; Drain Fluid Amylase